Destilador solar. (2020)
According to DANE figures, the coverage of drinking water is 92.3%, that is, there are more than 3.6 million people without access to the vital liquid of daily use. Not to mention the rural areas, where the lack of water supply exceeds 75% of coverage, the effects of climate change cause water shortages and thus leads us to seek alternatives with renewable energy to process water through the method of evaporation and condensation. In order to help with this problem in this project presents a type of solar distiller to generate distilled water, we want to increase its efficiency and performance in liters of water per day with the help of a parabolic solar concentrator compound developed at the facilities of the University Antonio Nariño in Tunja in the year 2019. In order to reach the objective, a bibliographic review on technologies in solar distillers was carried out, and it was determined that this method works easily but with low efficiencies. The project consists of an energy source which is the parabolic concentrator; a heat-resistant glass container evaporator with a copper spiral duct inside; a condenser which is a thermally insulated steel tank and a copper heat exchanger inside; and thus be able to obtain distilled water from water with sodium chloride. According to the results obtained in the thesis "Development of a Parabolic Compound Solar Concentrator" it is 110°C at the focal point and therefore due to the calculations made this temperature is not sufficient for the system to operate under good distillation performance conditions and it is concluded that the distiller needs a larger heat source.